Pengaruh Sikap dan Pengetahuan Keuangan Di Kota Langsa : Dampak Manajemen Keuangan Pribadi dan Gender Sebagai Variabel Moderating - Ulya, Zikriatul; Aisyah Putri; Syamsul Rizal; Aya Zulfia4; Muarif Setiawan (Journal Of Islamic Economics And Finance, 2025)
This study aims to analyze the effect of financial attitudes and knowledge on personal financial management among students in Langsa City, with gender as a moderating variable. Using a quantitative descriptive approach with a sample of 200 students selected through purposive sampling, the data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results show that attitudes and financial knowledge have a positive and significant effect on personal financial management, both partially and simultaneously. In addition, gender moderates the relationship between these two variables, indicating that psychological, cognitive, and demographic factors play an important role in shaping students' financial behavior. These findings contribute theoretically to the understanding of financial behavior and provide practical recommendations for educational institutions to develop gender-sensitive financial literacy programs.